2021
DOI: 10.1136/bmjgast-2020-000590
|View full text |Cite
|
Sign up to set email alerts
|

The value of anal swab RT-PCR for COVID-19 diagnosis in adult Indonesian patients

Abstract: ObjectiveThis study will test the performance of the anal swab PCR test when compared with the nasopharyngeal swab PCR test as a diagnostic tool for COVID-19.DesignAn observational descriptive study which included hospitalised suspected, or probable cases of hopitalised COVID-19 patients, conducted in Dr. Cipto Mangunkusumo National Hospital, Ciputra Hospital, Mitra Keluarga Depok Hospital and Mitra Keluarga Kelapa Gading Hospital, Indonesia. Epidemiological, clinical, laboratory and radiology data were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…The sensitivity and specificity of faecal samples as compared to pharyngeal samples obtained from this study goes to affirm that indeed, faecal samples could possibly be used in place of pharyngeal samples. This agreed with other studies carried out by Abdullah M et al, (2021) and Jeong et al, (2020) when it comes to the sensitivity and specificity of using faeces to test for the presence of SARS-CoV 2.…”
Section: Sensitivity and Specificity Of Using Faeces To Test For Sars-cov 2 As Compared Tosupporting
confidence: 91%
“…The sensitivity and specificity of faecal samples as compared to pharyngeal samples obtained from this study goes to affirm that indeed, faecal samples could possibly be used in place of pharyngeal samples. This agreed with other studies carried out by Abdullah M et al, (2021) and Jeong et al, (2020) when it comes to the sensitivity and specificity of using faeces to test for the presence of SARS-CoV 2.…”
Section: Sensitivity and Specificity Of Using Faeces To Test For Sars-cov 2 As Compared Tosupporting
confidence: 91%
“…Real-time quantitative reverse transcriptase-polymerase chain reaction (RT-qPCR) is the gold-standard laboratory technique for the identification of SARS-CoV-2 in the clinical setting, and nasopharyngeal swabs are considered the primary sample for COVID-19 tests with a sensitivity of around 70–80% [ 38 , 39 , 40 ]. However, false negative results are also possible [ 38 , 41 ], and other specimens, including fecal viral testing that has a high specificity to detect SARSCoV-2 despite a low sensitivity ranging from 37% to 60%, have also been considered [ 42 , 43 ]. However, some studies demonstrated that the clearance time of COVID-19 in the digestive tract was later than that in the respiratory tract [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies used anal swabs to diagnose COVID-19 ( Abdullah et al, 2021 , Li et al, 2021 ). However, it is not recommended to be used as a standalone test.…”
Section: Types Of Specimensmentioning
confidence: 99%
“…The abovementioned specimen types are variable for their diagnostic accuracy; sample collection or handling, the amount of viral load in the specimen, severity, or time from the onset of infection are all factors that would affect the accuracy of diagnosis ( Coden et al, 2020 , Abdullah et al, 2021 , Ling et al, 2020 , Senok et al, 2020 ). Some researchers noticed variabilities when testing different specimens from the same patient ( Li et al, 2021 , Xiao et al, 2020 , Senok et al, 2020 ).…”
Section: Types Of Specimensmentioning
confidence: 99%